A European, prospective, observational study of enzalutamide in patients with metastatic castration‐resistant prostate cancer: PREMISE. Issue 5 (8th November 2021) - Payne, Heather; Robinson, Angus; Rappe, Bernard; Hilman, Serena; De Giorgi, Ugo; Joniau, Steven; Bordonaro, Roberto; Mallick, Stéphane; Dourthe, Louis‐Marie; Flores, Moisés Mira; Gumà, Josep; Baron, Benoit; et al.
Abstract: In randomized clinical trials, the androgen‐receptor inhibitor enzalutamide has demonstrated efficacy and safety in metastatic castration‐resistant prostate cancer (mCRPC). This study captured efficacy, safety and patient‐reported outcomes (PROs) of enzalutamide in mCRPC patients in a real‐world European setting. PREMISE (NCT0249574) was a European, long‐term, prospective, observational study in mCRPC patients prescribed enzalutamide as part of standard clinical practice. Patients were categorized based on prior docetaxel and/or abiraterone use. The primary endpoint was time to treatment failure (TTF), defined as time from enzalutamide initiation to permanent treatment discontinuation for any reason. Secondary endpoints included prostate‐specific antigen (PSA) response, time to PSA progression, time to disease progression and safety. PROs included EuroQol 5‐Dimension, 5‐Level questionnaire, Functional Assessment of Cancer Therapy—Prostate and Brief Pain Inventory—Short Form. Overall, 1732 men were enrolled. Median TTF with enzalutamide was 12.9 months in the chemotherapy‐ and abiraterone‐naïve cohort (Cohort 1) and 8.4 months in the postchemotherapy and abiraterone‐naïve cohort (Cohort 2). Clinical outcomes based on secondary endpoints also varied between cohorts. Cohorts 1 and 2 showed small improvements in health‐related quality of life and pain status. The proportions of patients reporting treatment‐emergent adverse events (TEAEs) were 51.0% and 62.2% in Cohorts 1 and 2, respectively; enzalutamide‐related TEAEs were similar in both cohorts. The most frequent TEAE across cohorts was fatigue. These data from unselected mCRPC patients in European, real‐world, clinical‐practice settings confirmed the benefits of enzalutamide previously shown in clinical trial outcomes, with safety results consistent with enzalutamide's known safety profile. Abstract : What's new? In clinical trials, the androgen‐receptor inhibitor enzalutamide has demonstrated efficacy and safety in metastatic castration‐resistant prostate cancer (mCRPC). However, results in the real world may differ from those in controlled studies. This large, prospective study thus assessed unselected mCRPC patients with different prior treatment histories, who were then treated with enzalutamide. The results confirm and validate the benefits of enzalutamide in real‐world, clinical‐practice settings that were previously seen in clinical‐trial outcomes. These include improved health‐related quality of life (HRQoL).